2022
DOI: 10.1186/s12967-022-03326-6
|View full text |Cite
|
Sign up to set email alerts
|

Two for one: targeting BCMA and CD19 in B-cell malignancies with off-the-shelf dual-CAR NK-92 cells

Abstract: Background Chimeric antigen receptor (CAR) T-cell therapy has proven to be a valuable new treatment option for patients with B-cell malignancies. However, by applying selective pressure, outgrowth of antigen-negative tumor cells can occur, eventually resulting in relapse. Subsequent rescue by administration of CAR-T cells with different antigen-specificity indicates that those tumor cells are still sensitive to CAR-T treatment and points towards a multi-target strategy. Due to their natural tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 77 publications
0
16
0
Order By: Relevance
“…mRNA transfection is also considered to be a safe and practical transfection method for CAR-NK cells. In a xenograft tumor model, receptor expression exceeded 80% at 24h after electroporation of mRNA, and NK cells transfected with mRNA exerted marked cytotoxicity ( 92 ). Studies have recently shown that mRNA transfection avoids targeted non-tumor toxicity, a major limiting factor in the clinical application of CAR-modified cell immunotherapy ( 92 , 93 ).…”
Section: Combined Applications Of Car-nk Cells and Immune Checkpoint ...mentioning
confidence: 99%
See 1 more Smart Citation
“…mRNA transfection is also considered to be a safe and practical transfection method for CAR-NK cells. In a xenograft tumor model, receptor expression exceeded 80% at 24h after electroporation of mRNA, and NK cells transfected with mRNA exerted marked cytotoxicity ( 92 ). Studies have recently shown that mRNA transfection avoids targeted non-tumor toxicity, a major limiting factor in the clinical application of CAR-modified cell immunotherapy ( 92 , 93 ).…”
Section: Combined Applications Of Car-nk Cells and Immune Checkpoint ...mentioning
confidence: 99%
“…In a xenograft tumor model, receptor expression exceeded 80% at 24h after electroporation of mRNA, and NK cells transfected with mRNA exerted marked cytotoxicity ( 92 ). Studies have recently shown that mRNA transfection avoids targeted non-tumor toxicity, a major limiting factor in the clinical application of CAR-modified cell immunotherapy ( 92 , 93 ). However, the anti-tumor effect of CAR-NK cells transfected with mRNA by electroporation is temporary because the expression of CARs does not exceed 3 days.…”
Section: Combined Applications Of Car-nk Cells and Immune Checkpoint ...mentioning
confidence: 99%
“…A good efficacy has been demonstrated in early-phase clinical trials with bispecific CAR-Ts that target BCMA, CD19, or CD38 [112] . Future alternative approaches could be represented by allogenic BCMA CAR-T cells or CAR-NK (CARnatural killer), which are now investigated in early clinical trials [113][114][115][116][117][118][119][120][121] .…”
Section: Bcma Car-tsmentioning
confidence: 99%
“…There are a series of activated receptors but almost no inhibitory killer receptors expressed on NK-92 cells, and NK-92 cells are unable to mediate ADCC because of shortage of the CD16 receptor [ 143 – 145 ]. CAR-engineered NK-92 cells have strong cytotoxicity and can obtain a large number of cells with the same phenotypes in a short time [ 86 , 146 ]. The disadvantage of CAR-NK92 cells is that they must be irradiated to avoid malignant proliferation before infused into patients [ 83 ].…”
Section: Advantages Of Car-nk Immunotherapymentioning
confidence: 99%